Development of an in-line magnetometer for flow chemistry and its demonstration for magnetic nanoparticle synthesis. Issue 19 (18th August 2021) - Besenhard, Maximilian O.; Jiang, Dai; Pankhurst, Quentin A.; Southern, Paul; Damilos, Spyridon; Storozhuk, Liudmyla; Demosthenous, Andreas; Thanh, Nguyen T. K.; Dobson, Peter; Gavriilidis, Asterios
Abstract : A highly sensitive magnetometer for flow chemistry to characterise magnetic nanoparticles in solution, in situ and in real-time is presented. This facilitates continuous quality control and high-throughput screening of magnetic nanoparticle syntheses. Abstract : Despite the wide usage of magnetic nanoparticles, it remains challenging to synthesise particles with properties that exploit each application's full potential. Time consuming experimental procedures and particle analysis hinder process development, which is commonly constrained to a handful of experiments without considering particle formation kinetics, reproducibility and scalability. Flow reactors are known for their potential of large-scale production and high-throughput screening of process parameters. These advantages, however, have not been utilised for magnetic nanoparticle synthesis where particle characterisation is performed, with a few exceptions, post-synthesis. To overcome this bottleneck, we developed a highly sensitive magnetometer for flow reactors to characterise magnetic nanoparticles in solution in-line and in real-time using alternating current susceptometry. This flow magnetometer enriches the flow-chemistry toolbox by facilitating continuous quality control and high-throughput screening of magnetic nanoparticle syntheses. The sensitivity required to monitor magnetic nanoparticle syntheses at the typically low concentrations (<100 mM of Fe) was achieved by comparing the signals induced in the sample and reference cell, each of which contained near-identical pairs of induction and pick-up coils. The reference cell was filled only with air, whereas the sample cell was a flow cell allowing sample solution to pass through. Balancing the flow and reference cell impedance with a newly developed electronic circuit was pivotal for the magnetometer's sensitivity. To showcase its potential, the flow magnetometer was used to monitor two iron oxide nanoparticle syntheses with well-known particle formation kinetics, i.e., co-precipitation syntheses with sodium carbonate and sodium hydroxide as base, which have been previously studied via synchrotron X-ray diffraction. The flow magnetometer facilitated batch (on-line) and flow (in-line) synthesis monitoring, providing new insights into the particle formation kinetics as well as, effect of temperature and pH. The compact lab-scale flow device presented here, opens up new possibilities for magnetic nanoparticle synthesis and manufacturing, including 1) early stage reaction characterisation 2) process monitoring and control and 3) high-throughput screening in combination with flow reactors.